PIROLISIS SABUT KELAPA (Cocos nucifera L) MENGGUNAKAN INSTRUMEN PYROLYSIS-GAS CHOMATOGRAPHY/MASS SPECTROMETRY (PY-GC/MS) - Noor Afdaliah; RR Dirgarini Julia Nurlianti Subagyono; Veliyana Londong Allo (PROSIDING SEMINAR KIMIA, 2022)
Pyrolysis of a coconut (Cocos nucifera L) husk using a pyrolysis-gas chromatography-mass spectrometry (Py-GC/MS) instrument was carried out. This research was conducted to determine the chemical composition of pyrolysis of a coconut husk at temperaturs of 350, 450 and 550 °C. Pyrolysis of coconut husk produced lignin derivative products by 15-32% and cellulose/hemicellulose derivative products 9-34%. The gas product produced in the co-pyrolysis of a mixture microalgae anda coconut fiber is 41-50%. Pyrolysis product with the highest % area, namely methyl alcohol, 2-butanone, phenol, benzofuran, 2,3-dihydro- dan 2-methoxy-4-vinylphenol Keywords: Co-pyrolysis, Py-GC/MS dan coconut husk